Tapestry of fortunes [compact disc, unabridged] : a novel - Berg, Elizabeth (Recorded Books, 2013)
Motivational speaker Cecilia Ross, who encourages others to change their lives for the better, realizes that she needs to make changes in her life because she is still reeling from the death of her best friend. Downsizing her life, she sells her suburban home and lets go of many of her possessions, She moves into a beautiful old house in Saint Paul, complete with a garden, chef's kitchen, and three housemates All four women embark on a journey together in an attempt to connect with parts of themselves long denied.